Hounsfield unit value on CT as a predictor of cage subsidence following stand-alone oblique lumbar interbody fusion for the treatment of degenerative lumbar diseases - Jing Zhou (BMC, 2021)
Abstract Background To investigate the correlation between vertebral Hounsfield unit (HU) values and cage subsidence in patients treated with stand-alone (SA) OLIF. Methods A retrospective review of collected data was performed on 76 patients who underwent SA OLIF. We utilized the HU value for lumbar bone mineral density (BMD) obtained on preoperative CT. The vertebral HU values of patients with subsidence were compared to those without subsidence. The correlation between cage subsidence and clinical score was investigated. Results Sixteen patients (21.1%) had at least radiographic evidence of interbody cage subsidence. The average cage subsidence was 2.5 ± 1.3 mm (range 0.9-4.8 mm). There were no significant differences in sex, BMI, preoperative diagnoses, or fused level (p > 0.05); however, there were significant differences between the cage subsidence group and the nonsubsidence group in age, average of the lowest T-score, and average HU value, including for the L1 vertebrae, L1-L4 horizontal plane, and L1-L4 sagittal plane (p < 0.05). The average HU value of the L1-L4 horizontal plane showed a more predictable AUC of 0.909 (95% CI, 0.834–0.984; P < 0.001) compared with the average of the lowest T-score following an AUC of 0.791 (95% CI, 0.674–0.909; P < 0.001). Based on logistic regression analysis, the average HU value of the L1-L4 horizontal plane (OR, 0.912; 95% CI, 0.861–0.966; P = 0.002) was an independent factor influencing cage subsidence. Conclusions Patients with lower average HU values of the lumbar vertebrae are at a much higher risk of developing cage subsidence after SA OLIF. Measurement of preoperative HU values on preexisting CT scans could be rapid, simple and feasible.